Potential predictors for prognosis and postpartum recovery time of acute fatty liver of pregnancy - Jun Chen; Ze-Bing Huang; Xue-Gong Fan; Xing-Wang Hu; Min Qi; Cheng-Jin Liao; Li-Yuan Long; Yan Huang (BMC, 2020)
Abstract Background Acute fatty liver of pregnancy (AFLP) is a potentially lethal condition of pregnant women with a high mortality rate. Potential predictors related to postpartum recovery time and prognostic factors of AFLP are still unclear. This study aimed to evaluate potential predictors for prognosis and postpartum recovery time of AFLP. Methods We retrospectively analyzed the clinical data of 76 AFLP patients in our hospital from 2002 to 2017 and investigated potential predictors using univariate analysis and multivariate logistic regression analysis. Results Hepatic encephalopathy (HE) was found to be associated with prognosis in AFLP patients (P = 0.005, OR = 26.844). The postpartum recovery time analysis showed that AFLP patients with a age < 25 had the shortest recovery time, but no significant difference (P = 0.134, OR = 5.952). The postpartum recovery time of patients with liver failure (LF) was significantly prolonged compared to those without LF (P = 0.036, OR = 10.052). Cryoprecipitate, and plasma infusion showed no significant effect on prognosis or recovery time. Artificial liver support therapy (ALST) had no effect on prognosis, but it might affect postpartum recovery time with no statistical significance (P = 0.128, OR = 5.470). Conclusion HE is a potential predictor for prognosis of AFLP. LF is a potential predictor for postpartum recovery time.